(untitled) (Международный научный журнал «Инженер», 2026)
The results of studying the natural zeolite from the Beltau deposit are presented. To determine the comparative relationship between the characteristics of natural zeolite obtained from the Beltau deposit and mineral additives in the Uzbekistan construction materials market, natural zeolitic marl, microsilica, and metakaolin from the Beltau deposit were used. It was established that the W/T ratio of the studied powders increases in the following sequence: Beltau zeolite, crushed sand, microsilica, zeolite-containing marl, and metakaolin. Based on the rheological parameters of water-mineral pastes, the yield stress was calculated, and their plasticizing sensitivity to solvents of various chemical natures was determined. It was found that the pozzolanic activity of natural zeolite for CaO absorption is equal to 510 g/l; a change in the pH of the hydrating zeolite-cement suspension was observed, with its value decreasing to 12.7. Fine-grained cement concretes with strengths ranging from 75 to 86 MPa were obtained using natural zeolite from the Beltau deposit at concentrations of 5 and 10%.